1978
DOI: 10.1111/j.1432-1033.1978.tb12423.x
|View full text |Cite
|
Sign up to set email alerts
|

The Dicyclohexylcarbodiimide-Binding Protein of Rat Liver Mitochondria as a Product of the Mitochondrial Protein Synthesis

Abstract: A product of mitochondrial protein synthesis in rat liver mitochondria, characterized by a low molecular weight ( M , < 10000) and an unusually high hydrophobicity, has been identified as the dicyclohexylcarbodiimide-binding protein and as a peptide of the hydrophobic sector of the mitochondrial ATPase complex. The purified protein still possesses the ability to bind dicyclohexylcarbodiimide.Since the first report by Beechey et al. [l] that dicyclohexylcarbodiimide inhibits oxidative phosphorylation, there ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1979
1979
1986
1986

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The biogenesis of this subunit has been studied in yeast (2, 5), Neurospora (1), and in higher eukaryotes (15,16). In yeast this polypeptide is coded for by a mitochondrial gene, which has been isolated and sequenced, and is translated on mitochondrial ribosomes (17,18).…”
mentioning
confidence: 99%
“…The biogenesis of this subunit has been studied in yeast (2, 5), Neurospora (1), and in higher eukaryotes (15,16). In yeast this polypeptide is coded for by a mitochondrial gene, which has been isolated and sequenced, and is translated on mitochondrial ribosomes (17,18).…”
mentioning
confidence: 99%
“…Further confirmation of the site of synthesis of this protein is given by the fact that the N terminus is not formylmethionine, as is the case for the dicyclohexylcarbodiimide-binding component of yeast [14]. Recently, it has been reported that the dicyclohexylcarbodiimide-binding protein of rat liver mitochondria is a mitochondria1 product, though the protein was not clearly resolved on gels, and end group determination was not carried out as a check for purity [32]. It is possible that a low-molecular-weight mitochondrial translation product(s), extractable from a trichloroacetic acid precipitate of whole mitochondria by chloroform/methanol and similar to that of A .…”
Section: Dicyclohexylcarbodiimide-binding Proteinmentioning
confidence: 99%
“…These studies confirm earlier work on the biogenesis of the ATPase in these THE JOURNAL OF CELL BIOLOGY " VOLUME 86 SEPTEMBER 1980 723-729 © The Rockefeller University Press -0021-9525/80/09/0723/07 $1 .00 organisms (23,49,50) . There are conflicting reports on the site of biosynthesis of the DCCD-binding protein in animal cells (1, 12,13,25).…”
mentioning
confidence: 99%